Clinical Supervision in Education - Khasanah, Tatiatun; Maryam, Sinta; Safitri, Triani Dwi (Proceedings Series on Social Sciences & Humanities, 2025)
The low quality of learning at various levels of education is a serious challenge in improving the effectiveness of the overall learning process, which until now has been a major concern in the world of education. Therefore, to overcome these challenges, clinical supervision is present as a focused approach, recognized as having significant potential in developing teacher professionalism and improving the quality of teaching continuously. This study aims to collaborate and synthesize concepts, existing models, and the effectiveness of clinical supervision as reported in the scientific literature. Furthermore, this study also seeks to identify challenges and opportunities for implementing clinical supervision based on an in-depth analysis of academic publications. By applying the systematic literature review method, a large number of relevant scientific articles from various reputable databases have been comprehensively reviewed and analyzed. The results of the literature synthesis consistently highlight that effective clinical supervision is characterized by a structured collaborative process between supervisors and teachers, centered on teaching observations, providing constructive feedback, and formulating specific improvement plans. The literature also shows that various models of clinical supervision have been proven to be able to improve teacher pedagogical competence, encourage continuous performance improvement, and promote a culture of self-reflection in the school environment. However, this literature review also identified several common barriers to implementation, including time constraints, lack of adequate training for supervisors, and potential resistance from teachers. This literature review provides an important contribution to an evidence-based understanding of the dynamics of clinical supervision, which can inform the development of more effective and adaptive educational policies and practices.